Analysis of User Acceptance Towards The Implementation of Information Systems in Financial Institutions Using Technology Readiness and Acceptance Model Approach - Mahesa Yahya, Lucky; Rasyiddin, Ahmad; Muhlasin; Mariko, Selli; Harsono, Iwan (Jurnal Informasi dan Teknologi, 2024)
This research aims to measure the influence of user acceptance and readiness on implementing information systems. Researchers conducted this research using a quantitative approach. Researchers collected samples using a multi-stage purposive sampling strategy. There were one hundred participants in the study's sample. This study used two data collection methods: unstructured interviews were conducted to gather supporting data for the research, and questionnaires were distributed to get primary data. Inferential statistical analysis was performed in this study utilizing the PLS-SEM approach with SmartPLS. At this point, two analyses, the measurement model analysis, and the structural model analysis, must be completed. These findings indicate that sentiments of optimism and inventiveness positively impact opinions about the advantages and usability of information systems. This factor encourages users' interest in accepting or continuing to use the information system so that it will have a good influence on its implementation. On the other hand, user discomfort in using information systems tends to negatively influence assessments of the benefits and ease of use of information systems. User discomfort in using information systems hinders users' interest in using the information system, which impedes implementing the information system. The insecurity factor did not influence the assessment of the benefits and ease of use of information systems. These findings have several differences from previous research.